The Political and Economic Situation of Iceland in the Context of EU Application Withdrawal - Lidia Pokrzycka (Politeja, 2017)
Under the influence of the crisis of 17 July 2009, Iceland presented its application for accession to the European Union, and a year later began accession negotiations. However, a problematic issue is catch limits as instead of 200‑mile fishing belt they won during the Cod Wars there would be just 12 miles of fisheries intended for Icelanders. Therefore, the accession negotiations stood at a standstill, the more that the current situation of the euro does not encourage Iceland to join the EU. Recently it turned out that Iceland does not want to join the European Union. In this article, I introduce arguments for and against Iceland joining the European Union. I introduce the economic, political and social situation in Iceland based on my own research on the island from 2010. In 2013, I completed a journalism internship in the editorial team of the Icelandic weekly Reykjavik Grapevine.